Factors That Influence the Use of Accounting Information Systems - Ni Putu Lisa Ernawatiningsih; I Putu Edy Arizona (AIBPM Publisher, 2023)
The quality of the company's annual financial reports does not only depend on the company's personal factors but also on the effectiveness of the use of systems. From an economic point of view, the people of Sukawati are more involved in trading. Therefore, the existence of a village lending institution is necessary to support the business capital. This study aims to determine the effectiveness of applying accounting information systems. Village Bank is a village-owned financial institution that performs financial functions and manages the funds belonging to the village in the form of savings and loans. It sets out the goals for investigating the factors that influence the effectiveness of using accounting systems. The research approach uses a sampling approach that involves multiple linear regression evaluations and the use of random samples of interest. These survey patterns are staff using accounting data gadgets in credit status organizations in the Skawati district village. The results indicate that individual skills, user involvement, internal control, and organizational culture have positive effect to use Accounting Information Systems. This research is expected to strengthen the function of the accounting information system in order to avoid all forms of fraud through factors that have a significant effect on this research.